ON THE TUNA CONSERVATION IN THE ATLANTIC - Paiva, Melquíades Pinto (Arquivos de Ciências do Mar, 2018)
The exploitation of tuna resources in the oceamc waters of the Atlantic was introduced on a large scale only recently, with the arrival of Japanese long-line vessels in 1956